Administrative Administration in Improving the Quality of the Teaching and Learning Process at Letris Bintaro Vocational High School - Ayi Najmul Hidayat; Indah Marita Sari (FKIP - Universitas Riau, 2026)
Vocational High Schools (SMK) face increasingly complex challenges due to the demands for integration between education and industry. However, improving the quality of education is often focused on teacher performance in the classroom, while the strategic role of school administration is often overlooked. This study aims to analyze the role of Administrative Administration (TU) in improving the quality of the Teaching and Learning Process (PBM) at SMK Letris Bintaro by integrating Henry Fayol's management theory and Ralph Tyler's curriculum model. This study uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, passive participant observation, and documentation studies involving the principal, the Head of Administration, administrative staff, and teachers. The results show that the application of Fayol's management functions, particularly organizing, division of labor, and the principle of order, improves the efficiency of academic services. TU administration also plays a significant role in supporting the components of Tyler's model, particularly in providing learning experiences, organizing facilities, and ensuring the accuracy of evaluations. Orderly and responsive administrative services have been shown to reduce the administrative burden on teachers, thereby supporting improved learning quality.